Solid Phase Extraction and Determination of Nickel in Water Samples by Using Novel Thiol-Containing Sulfonamide Polymeric Resin and Atomic Absorption Spectrophotometer - Karaaslan, Nagihan M.; Senkal, B. Filiz; Er, Cigdem; Avci, Halim; Yaman, Mehmet (Office Spectroscopy & Spectral Analysis, 2011)
Interest in preconcentration techniques for the determination of metals at ultratrace levels still continues increasingly because of some disadvantages of flameless atomic absorption spectrometry as well as the high costs of other sensitive methods in compared to flame atomic absorption spectrometry. In this study, thiol-containing sulfonamide resin was synthesized, characterized and applied as a new sorption material for solid phase extraction of nickel in drinking water samples. After preconcentration procedure, flame atomic absorption spectrometry was used for determinations. Optimum parameters were found to be pH=3. 2, contact time =20 min and eluate volume=3 mL. The limit of detection was found to be 0. 75 ng . mL(-1). The synthesized resin exhibits the superiority in compared to the other adsorption reagents because of the fact that there is no necessity of any complexing reagent, high sorption capacity as well as the relatively fast extraction rate. The Ni concentrations in the studied 21 kind of water samples were found to be in the range of BDL-4. 0 ng . mL(-1).
Keywords: Spectroscopy; Extraction; Nickel; Preconcentration; Atomic absorption